Land suitability models for rubber in moneragala district: First approximation using GIS - Karunaratne Senani; Gunathilake Jagath; Herath Kemenda; samarappuli Lalani; Wijesuriya Wasana (Journal of the Rubber Research Institute of Sri Lanka, 2011)
Rubber is one of the major plantation crops grown in Sri Lanka, which generates foreign earnings to the country. To cope up with the increasing demand for rubber in both local and international markets it is vital to increase the extent under rubber cultivation. Expansion of rubber into intermediate and dry zone areas of Sri Lanka is focused in rubber development activities to acieve the national production targets. hence, the objective of this study is to develop a land suitability map for rubber in Moneragala district and to identify potential land uses for further expansion of rubber in this district. The study was carried out in GIS environment using weighted overlaying technique. Results from the suitability analysis revealed that, the DS division, Madulla has the highestextent of most suitable category (1289 ha) while Wellawaya and Siyambalanduwa have 480 ha and 476 ha, respectively. The information derived through this study offer a ground for the policy makers for effective decision making on expanding rubber cultivation in the Moneragala district.
Keywords: GIS; Land suitability modeling; Moneragala district